Oral Sex, Semen Displacement, and Sexual Arousal: Testing the Ejaculate Adjustment Hypothesis - Michael N. Pham; Todd K. Shackelford; Lisa L. M. Welling; Alyse D. Ehrke; Yael Sela; Aaron T. Goetz (Evolutionary Psychology, 2013)
Male Indian Flying Foxes ( Pteropus giganteus ) that spend more time performing oral sex on a female also spend more time copulating with her. In humans, men who spend more time copulating with their regular partner also perform more “semen-displacing” copulatory behaviors (e.g., deeper, more vigorous penile thrusting). We investigated whether men who spend more time performing oral sex on their regular partner also spend more time copulating with her and perform more semen-displacing copulatory behaviors. We proposed and tested the ejaculate adjustment hypothesis for men's copulatory behaviors: Men adjust their copulatory behaviors to increase their sexual arousal and consequent ejaculate quality, thereby increasing their chances of success in sperm competition. Two hundred and thirty-three men in a committed, heterosexual relationship responded to questions about their copulatory behavior and sexual arousal during their most recent sexual encounter with their long-term partner. The results indicated that men who spend more time performing oral sex on their partner also spend more time copulating with her, perform more semen-displacing copulatory behaviors, and report greater sexual arousal. We discuss limitations to the current research and highlight the heuristic value of sperm competition theory for understanding human sexual behaviors.